The Relationship Between Knowledge and Attitudes About Reproductive Health with Adolescent Sexual Behavior at Ponorogo in 2017 - Esti Sugiyorini (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2019)
Introduction: Reproductive health is a state of overall health related to the reproductive system. Adolescent group is the group that have most of risk in reproductive health, because there is a very large of physical change, that is maturation of reproductive organs and functions. Adolescents begin to feel a sexual urge and are attracted to other geneder so they are have risk of unwanted pregnancy, abortion and HIV / AIDS. The purpose of this study is to find out of knowledge and attitudes about reproductive health and its relationship with sexual behavior in adolescents. Methods: This research was cross sectional study. Population’s study were all of 1st grade students of Senior High School Sooko 1 Ponorogo (70 students) with 60 studets for sample. The sampling technique used was simple random sampling. The instrument in this study was a questionnaire. Data were collected by giving questionnaires and interviews to the sample group. Data were analyzed with Fisher exact test. Results: Fisher Exact Test was showed p> 0.05 for the relationship between reproductive health knowledge and sexual behavior of students and and the Fisher Exact Test was also showed p> 0.05 for the relationship between sexual behavior and students' attitudes toward reproductive health. Conclusion: There did not have relationship between knowledge of reproductive health with sexual behavior and also did not have relationship between sexual behavior with reproductive health attitudes in students. Keywords: knowledge; attitudes; sexual behavior; reproductive health; adolescents